A review on inhibitors alleviating copper corrosion in hostile simulated Sea-water (3.5 wt.% NaCl solution). (2021) - Pareek, Shubhra; Jain, Deepti; Behera, Debasis; Sharma, Sachin; Shrivastava, Rahul
Abstract: Approximately all-metallic structure is manufactured from the copper metal. The application of neutral environmental condition is generally found in the heat exchange system of desalination plants where aggressive chloride ions cause pitfalls on the metal surface. This review paper precisely inspects corrosion inhibitors (CI) in hostile corrosive environments i.e., simulated sea-water (3.5 wt.% NaCl solution) for the protection of copper metal from corrosion. The emphasis has been given to nitrogen-containing synthetic heterocyclic inhibitors due to their better protection ability and effectiveness. The literature furnishes the understanding of the diverse behavior of inhibitors and their performance in a particular environment. The motive of this literature is to present the most suitable organic inhibitors with higher polarization efficiencies in the corrosive environment.